"In the Image of God": Reconstructing and Developing a Grassroots African Queer Theology from Urban Zambia. Issue 1 (January 2015) - van Klinken, Adriaan; Phiri, Lilly
Abstract : This article is a contribution towards the development of queer theologies in contemporary African contexts. Based on fieldwork in the gay community in Lusaka, the capital city of Zambia, the article explores the significance of the theological notion of the Imago Dei, the image of God, in the self-understanding of Zambian gay men as being gay and Christian. Bringing this incipient grassroots theology into conversation with broader theological discourses, in particular African theology (including African women's theology) and queer theology, we interrogate current understandings of the Imago Dei that either ignore sexuality or exclude same-sex loving people (in African theology) or that conceptualize queerness from white Western privileged perspectives (in queer theology). Hence we develop the notion of the Imago Dei as a stepping stone towards an African queer theology.